A Message for Peace or a Tool for Oppression? Israeli Jewish-Arab duo Achinoam Nini and Mira Awad’s Representation of Israel at Eurovision 2009 - Belkind, Nili (Current Musicology, 2010)
Israel’s contenders for the 2009 Eurovision Song Contest (known as the ESC or, as here, Eurovision) were the Israeli Jewish-Arab duo Achinoam Nini and Mira Awad. The chosen song was “There Must Be Another Way,” a tri -lingual appeal for peace and reconciliation sung in Hebrew, Arabic, and English. The decision to nominate Nini and Awad as Israel’s representatives to Eurovision was announced in early January, in the midst of a full-scale war Israel launched on Gaza and its inhabitants, which came in response to several years of rockets fired into Israel from the Hamas-led territory. Given the timing and the high profile of the ESC, an annual competition held among active member countries of the European Broadcasting Union (EBU), the duo’s collaboration generated much public debate in Israel and beyond. The debate highlighted the symbolic charge of the song and its performers, and it continued throughout the year, animated by the political situation, the duo’s activities, and the media that closely followed the process leading to the May 2009 contest and its aftermath. This article will analyze the meanings given to the artistic collaboration of the two performers that were circulating in the public sphere to show how, in this war-torn region, cultural and political domains are intertwined such that wars are fought not only with guns and rockets but also within cultural spheres, and that both domains are constitutive of highly contested social constructions of ethnic and national affiliations.